Evaluasi Response Time Transportation Emergency dalam Bencana Kebakaran di Kecamatan Bogor Tengah - Nugraha, Adrianto Fahrizal; Murtedjo, Tedy; Alimuddin (Journal of Applied Civil Engineering and Infrastructure Technology, 2024)
Bogor City spans 11,138 hectares with a population density of 9,548.00 people/km². The densest population resides in Central Bogor District, impacting fire risk. Over 2019-2022, there were 296 fire incidents, 15% occurring in Central Bogor District. The study aims to assess emergency car response times during fires in this district. Using qualitative descriptive methods, interviews and analysis per PERMENDAGRI Regulation No. 114 of 2018 were employed. Central Bogor District falls within the Emergency Management Zone (WMK) in Sukasari, Yasmin, and Cibuluh sectors due to being within a 7.5 km radius reachable within <15 minutes. The response time rate hit 100% out of 12 incidents in 2022, aligning with PERMENDAGRI Regulation No. 114 of 2018. Average speed is 60-80 km/h, dropping to 40 km/h during congestion. Sectors have efficient night routes. DISHUB's road network performance evaluation reveals V/C ratios of 0.54 and 0.48 (holidays) on Jl. Brigjen Saptadji Hadiprawira, Yasmin (holidays), and Jl. Raya Padjajaran 2, Sukasari. Cibuluh sector remains unaffected, enabling early fire disaster management.